2005
DOI: 10.1111/j.0014-3820.2005.tb01067.x
|View full text |Cite
|
Sign up to set email alerts
|

Parallel Evolution in Ecological and Reproductive Traits to Produce Cryptic Damselfly Species Across the Holarctic

Abstract: The damselfly genus Enallagma originated in the Nearctic, and two Nearctic lineages recently underwent radiations partly associated with multiple independent habitat shifts from lakes dominated by fish predators into lakes dominated by dragonfly predators. A previous molecular study of four Palearctic morphospecies and all representative Nearctic species identified the presence of two cryptic species sets, with each set having Palearctic and Nearctic representatives. However, the cryptic species within each se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
26
0
3

Year Published

2006
2006
2019
2019

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(30 citation statements)
references
References 63 publications
1
26
0
3
Order By: Relevance
“…Polydomy may, therefore, provide an interesting variation on the idea of behavioral convergence. Behavioral convergence is the repeated evolution of the same behavioral traits by species in similar environments (e.g., Blackledge and Gillespie 2004 ; Stoks et al 2005 ; Johnson et al 2010 ; Alejandrino et al 2011 ). In the case of polydomy, rather than the behavior evolving multiple times in response to similar ecological conditions, the same behavior may have evolved multiple times in response to a variety of different ecological conditions, due to an inherent predisposition for the behavior.…”
Section: Discussionmentioning
confidence: 99%
“…Polydomy may, therefore, provide an interesting variation on the idea of behavioral convergence. Behavioral convergence is the repeated evolution of the same behavioral traits by species in similar environments (e.g., Blackledge and Gillespie 2004 ; Stoks et al 2005 ; Johnson et al 2010 ; Alejandrino et al 2011 ). In the case of polydomy, rather than the behavior evolving multiple times in response to similar ecological conditions, the same behavior may have evolved multiple times in response to a variety of different ecological conditions, due to an inherent predisposition for the behavior.…”
Section: Discussionmentioning
confidence: 99%
“…Based on previous mass) Ϫ log (initial wet mass)]/4 e wet mass-to-dry mass regressions, we assumed that dry mass (McPeek 2004). Previous anal-mass p 0.15 # wet Stoks et al (2005b).…”
Section: Phenotypic Patternsmentioning
confidence: 99%
“…Functional studies have also identified ecologically important phenotypes that limit the distributions of species along this gradient and that influence population regulation (Pierce et al 1985;McPeek 1990aMcPeek , 1995aMcPeek , 1999McPeek , 2004McPeek et al 1996;Stoks and McPeek 2003a;Stoks et al 2003). Previous analyses have explored the diversification of Enallagma throughout the Holarctic (e.g., McPeek and Brown 2000;Stoks et al 2005b). Here, we focus on Lestes diversification and the comparison of the two genera in eastern North America, where most of our ecological work has been done.…”
mentioning
confidence: 99%
“…To a lesser extent, similar work has been done in invertebrate groups, specifically arthropods. For example, convergent or parallel evolution has been identified in replicated shifts of host use in insects [21,22], web construction in arachnids [8], larval morphology and antipredator behavior in aquatic insects [23], and adult morphology in barnacles [24]. Outside of arthropods, few studies using invertebrates explicitly test for convergence and parallelism (but see gastropods: [25,26]; bivalves: [27]).…”
Section: Introductionmentioning
confidence: 99%